DESKRIPSI PENERAPAN STANDAR PROSES DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP KOTA PALU - Rus'an Rus'an (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2016)
This type of study is descriptivequalitative aimed at describing Application Processing Standards (planning, implementation, assessment) in the learning of Islamic religious education by junior high school teacher who's been and yet Certified Educator. Results of this study were (1) The application of process standards in teaching Islamic religious education by teachers who are already Certified in (a) the administration of the learning plan declared well, (b) learning activities on the application of professional competence by the subject teacher 1, teacher 2 and teacher 3 obtaining good category, the application of pedagogical competence by subject teacher 1, teacher 2 and teacher 3 acquire assessment category Very Good, and (c) administrative assessment by the subject teacher 1 (aspects of assessment tools Well, aspects of the implementation of appraisal Fair, aspects of assessment results Good ), the subject of teacher 2 (aspects of assessment tools Very Good, aspects of the implementation of the Good, the aspect assessment Good), and teacher 3 (aspects of assessment tools Very Good, aspects of the implementation of the Good, the aspect assessment Good), (2) standard implementation process of learning Islamic religious education by teachers who are Not Certified Educator in (a) the administration of the learning plan declared Well, (b) learning activities on the application of professional competence by the subject teacher 5 and teacher 6 to obtain the category of Good and Teacher 4 acquire the category Fair, on the application of pedagogic by subject teacher 5 and teacher 6 to obtain the assessment categories Very Good and Teacher 4 to obtain the assessment categories Good, and (c) administrative assessment by subject teachers 5, teacher 6, and teacher 4 on aspects of assessment tools, aspects of the implementation of the assessment, aspects of assessment each obtain Good assessment category.Results of the research application process standards in teaching Islamic religious education in junior high school Palu by teachers who are already certified still need to be improved or not maximized as a whole, in certain cases still need attention and effort to optimize an integrated, systematic and effective according to the situation and conditions education unit and the local area